Generalized GN’-Function for n-Variable - Shubber, Hadeel (University of Thi-Qar Journal of Science, 2019)
In this work, we extend the usual theory of Orlicz spaces generated by real valued N-functions of a real variable. In particular, GN*-functions are the generalization of the variable N-functions used by Portnov and the non-decreasing -function by Wang